2016
DOI: 10.1038/boneres.2016.35
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced but hypofunctional osteoclastogenesis in an autosomal dominant osteopetrosis type II case carrying a c.1856C>T mutation in CLCN7

Abstract: Type II autosomal dominant osteopetrosis (ADO2), which is the most common form of osteopetrosis, is caused by heterozygous mutations in the chloride channel 7 (CLCN7) gene. The osteopetrosis of ADO2 has been attributed to hypofunctional osteoclasts. The mechanism underlying the abnormality in osteoclast function remains largely unknown. This study was designed to investigate gene mutations and osteoclast function in a case that was clinically diagnosed as ADO2. Genomic DNA was extracted from blood samples of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…It has been reported that perturbation of lysosomal function leads to alterations in the activity of cathepsin proteases such as CTSK. Not surprisinggly, we detected a remarkable decrease of CTSK in clcn7 morphants ( Figure 6B ), which was consistent with the previous report regarding the reduced expression of CTSK mRNA in ADO II patient 37.…”
Section: Resultssupporting
confidence: 93%
“…It has been reported that perturbation of lysosomal function leads to alterations in the activity of cathepsin proteases such as CTSK. Not surprisinggly, we detected a remarkable decrease of CTSK in clcn7 morphants ( Figure 6B ), which was consistent with the previous report regarding the reduced expression of CTSK mRNA in ADO II patient 37.…”
Section: Resultssupporting
confidence: 93%
“…Precursor cells of osteoclasts (OCs) from human peripheral blood were cultured as previously described . A 15 mL of heparin anticoagulated peripheral blood was obtained by venipuncture from the patient, and a healthy age‐ and sex‐matched control.…”
Section: Methodsmentioning
confidence: 99%
“…Our in vitro study clearly showed reduced osteoclast formation ability in this patient, 294 which is consistent with the reduced RANKL/OPG ratio. Based on our experience, in 295 vitro osteoclast culture could reliably reflect the osteoclast formation ability of humans 296 [38]. Although this patient had increased CTX levels, we believe he had inhibited bone 297 resorption as a result of decreased osteoclast formation, which is also consistent with formation, leading to increased bone mass ( Figure 5).…”
mentioning
confidence: 83%